Media Digital dalam Pendidikan Anak Usia Dini: Antara Inovasi Pedagogis dan Tantangan Etis - Irmawati, Irmawati; Herdiansyah, Erick; Arimbawan, Faizal; Priawasana, Endra (Jurnal Kridatama Sains dan Teknologi, 2025)
The development of digital media in early childhood education (ECE) presents both pedagogical opportunities and complex ethical challenges. This study aims to develop and evaluate a digital media model that balances educational innovation with child rights protection, focusing on the integration of teachers' digital literacy and child-friendly application design. A mixed methods approach with a convergent parallel design was employed, involving 12 teachers and 60 students from three ECE institutions in Jember Regency, along with 9 parents. Data were collected through semi-structured interviews, participatory observation, and document analysis, and analyzed using thematic techniques and descriptive statistics with NVivo 14 and SPSS version 26. The findings indicate that digital media usage in ECE remains largely passive and lacks ethical consideration, while teachers and parents express strong needs for educational and safe media. Interventions in the form of ethical digital literacy training modules and a prototype of a play-based digital learning application improved teachers’ ethical awareness and children's active engagement in learning. The products were revised based on field evaluations to align with local contexts and user characteristics. This research contributes conceptually by proposing an ethical digital pedagogy model and provides practical recommendations for policy development, application design, and training for teachers and parents to build a safe, inclusive, and meaningful digital education ecosystem for young children